HLA Class Ia and Ib Polyreactive Anti-HLA-E IgG2a Monoclonal Antibodies (TFL-006 and TFL-007) Suppress Anti-HLA IgG Production by CD19+ B Cells and Proliferation of CD4+ T Cells While Upregulating Tregs - Ravindranath, Mepur H. (J Immunol Res, 2017)
The anti-HLA-E IgG2a mAbs, TFL-006 and TFL-007, reacted with all HLA-I antigens, similar to the therapeutic preparations of IVIg. Indeed, IVIg lost its HLA reactivity, when its HLA-E reactivity was adsorbed out. US-FDA approved IVIg to reduce antibodies in autoimmune diseases. But the mechanism underlying IVIg-mediated antibody reduction could not be ascertained due to the presence of other polyclonal antibodies. In spite of it, the cost prohibitive high or low IVIg is administered to patients waiting for donor organ and for allograft recipients for lowering antiallograft antibodies. A mAb that could mimic IVIg in lowering Abs, with defined mechanism of action, would be highly beneficial for patients. Demonstrably, the anti-HLA-E mAbs mimicked several functions of IVIg relevant to suppressing the antiallograft Abs. The mAbs suppressed activated T cells and anti-HLA antibody production by activated B cells, which were dose-wise superior to IVIg. The anti-HLA-E mAb expanded CD4+, CD25+, and Foxp(3)+ Tregs, which are known to suppress T and B cells involved in antibody production. These defined functions of the anti-HLA-E IgG2a mAbs at a level superior to IVIg encourage developing their humanized version to lower antibodies in allograft recipients, to promote graft survival, and to control autoimmune diseases.